Studi Fakor Resiko Kejadian Stunting Pada Balita Di Wilayah Dataran Tinggi Dan Dataran Rendah - Harlina Harlina; Healthy Hidayanty; Muh Ilyas Nur (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: nutritional problems are a global problem throughout the world. Malnutrition is an occurrence of wrong nutrition, it can be undernutrition or overnutrition. Globally, the incidence of stunting is still very high, including in Indonesia. Objective: to analyze the risk factors for stunting in children under five in the Highlands and Lowlands. Methods: The research used is quantitative with a case-control research design. The research location in Jeneponto Regency is divided based on the highland and lowland areas with a total sample of 76 studies (38 stunting toddlers and 38 normal toddlers) in the highland and lowland areas with a total sample of 152 toddlers aged 6-59 months. Data were processed using SPSS with univariate and bivariate analysis. Results: that the results show that the source of drinking water in the highlands (p=0.037; OR 2.676 (CI=1.049-6.829) is a risk factor for stunting. Conclusion: that the source of drinking water is a risk factor for stunting. So it is hoped that further checks will be made on drinking water quality in highland areas, providing education to families regarding drinking water management.